DAMPAK AKTIVITAS SOCIAL MEDIA MARKETING TERHADAP BRAND IMAGE, BRAND AWARENESS, BRAND TRUST, BRAND LOYALTY DAN WILLINGNESS TO PAY PADA BENGKEL DOKTER MOBIL - Radnan, Yokie; Fermin, Stephanus (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
The purpose of this study is to determine the relationship between social media and brand image, brand awareness, brand trust, brand loyalty, and Willingness to pay at a car doctor's workshop. The car doctor workshop is a workshop that is quite active in social media activities and the workshop can survive until now. I conducted this research in 2023, this research was conducted by distributing online questionnaires via google form to approximately 500 respondents and processing power using the SmartPLS application. The results in this study indicate that there is a relationship between social media on brand awareness, brand image, brand trust, brand loyalty, and positive Willingness to pay.